Teachers' Practices of Assessment in Secondary Level Mathematics - Bhattarai, Yubaraj (Academic Journal of Mathematics Education, 2021)
The purpose of my study was to find teachers' practices of assessment in mathematics at secondary level from 2005 AD to 2020 AD in the local context in Nepal. I conducted the study in Kavrepalanchok district in Nepal with a narrative research inquiry and interpretive paradigm under a qualitative research approach. The construction of assessment knowledge by in-service mathematics teachers as participants was the epistemology of my research, which tried to explain subjective perception through mental constructs. Interactions and communication among students contribute to the construction of reality. I conducted in-depth interviews using interview guidelines to excavate the narrative stories of respondent participants as a method of data collection. I transcribed the shared stories of the participants to generate themes using qualitative tools of data analysis. Five in-service teachers selected using a purposive sampling method from the district were the participants in the study. In-service mathematics teachers in Nepal are passionate about instilling curiosity and motivation in their students, and they are particularly interested in contextual assessment related to their daily activities. Sufficient feedback from the mathematics teachers has supported students to promote their mathematics learning. The study concluded that mathematics assessment practices provide multiple opportunities for teachers and students to transform their usual practices and establish classroom activities as a discourse for knowledge construction.